Politična socializacija, izobrazba in ambivalentnost politične profesionalizacije žensk - Rožman, Sara (Teorija in praksa, 2012)
Based on interviews with Slovenian male and female politicians, in this article the authors try to analyse two sets of factors of political professionalisation - early political education and socialisation as well as professional experience. These factors serve as the basis of male and female politicians´ competencies and skills, their autonomy in relation to a political party, as well as their freedom in exercising political views. The analysis of the interviews shows that women express discomfort towards professional politics and their political function more often and more explicitly than men. This discomfort and ambivalence is often mitigated by invoking their professionalism which stems from their education and experiencein previous professions.
Keywords: Politicians; Politiki; Političarke; Women politicians; Profesionalizacija; Professionalization; Politična socializacija; Political socialization; Spol (Psihologija); Sex (Psychology); Slovenia; Slovenija; politika; politics; woman; ženske